The challenge of global commons and flows for US power the perils of missing the human domain - Aaltola, Mika; Kapyla, Juha; Vuorisalo, Valtteri (Ashgate, 2014)
The book pays special attention to one of the least recognized but perhaps even fundamental challenges related to the Global Commons, namely the conceptual and practical challenge of inter-domain relationships-between maritime, air, space, and cyber-flows that brings about not only opportunities but also new vulnerabilities.